Legati legionis I Italicae. Prosopographic summary - Hatłas, Jerzy (Balcanica Posnaniensia. Acta et studia, 1990)
The article presents a prosopographical list of the legates of Legio I Italica in the Roman Empire. The problem is significant for studies on the command structure of the Roman army and senatorial careers. The aim of the work is to collect and organize all known and probable commanders of this legion. The author applies the prosopographical method, analyzing epigraphic and literary sources. The most important results indicate that 23 legates of Legio I Italica are known, some of whom can be precisely dated, while others remain uncertain. The article systematizes their careers (cursus honorum), origins, and social status. The conclusion emphasizes the importance of this military unit in Lower Moesia and the limitations of sources that hinder a full reconstruction of its command staff.